Preparation of ZnFe2O4/α-Fe2O3 Nanocomposites From Sulfuric Acid Leaching Liquor of Jarosite Residue and Their Application in Lithium-Ion Batteries - Yao, Jinhuan; Yan, Jing; Huang, Yu; Li, Yanwei; Xiao, Shunhua; Xiao, Jianrong (Frontiers in Chemistry, 2018)
Recycling Zn and Fe from jarosite residue to produce high value-added products is of great importance to the healthy and sustainable development of zinc industry. In this work, we reported the preparation of ZnFe2O4/α-Fe2O3 nanocomposites from the leaching liquor of jarosite residue by a facile chemical coprecipitation method followed by heat treatment at 800 °C in air. The microstructure of the as-prepared ZnFe2O4/α-Fe2O3 nanocomposites were characterized by X-ray diffraction (XRD), Mössbauer spectroscopy, scanning transmission electron microscope (STEM), and X-ray photoelectron spectrum (XPS). The results demonstrated that the ZnFe2O4/α-Fe2O3 composites are composed of interconnected ZnFe2O4 and α-Fe2O3 nanocrystals with sizes in the range of 20-40 nm. When evaluated as anode material for Li-ion batteries, the ZnFe2O4/α-Fe2O3 nanocomposites exhibits high lithium storage activity, superior cyclic stability, and good high rate capability. Cyclic voltammetry analysis reveals that surface pseudocapacitive lithium storage has a significant contribution to the total stored charge of the ZnFe2O4/α-Fe2O3, which accounts for the enhanced lithium storage performance during cycling. The synthesis of ZnFe2O4/α-Fe2O3 nanocomposites from the leaching liquor of jarosite residue and its successful application in lithium-ion batteries open up new avenues in the fields of healthy and sustainable development of industries.